Findbuch des Bestandes Abteilung 79: Ministerium für das Herzogtum Schleswig zu Kopenhagen 1851-1864 - Rathjen, Jörg (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2008)
The Ministry for the Duchy of Schleswig was established after the end of the Schleswig-Holstein census in 1851 and existed until 1864. The documents of the Ministry are divided between the Danish Imperial Archives in Copenhagen and the Schleswig-Holstein State Archives. The majority of the documents have been in the Imperial Archives since the exchange of German-Danish archival documents in 1933. In the Schleswig-Holstein State Archives, local individual files for the southern and central Schleswig-Holstein areas as well as the minutes of outgoing letters (descript journals, letter books) and transcripts (registries, copy books, correspondence records) can be found. The total duration of the collection extends from 1713 to 1871, with the focus of the documents covering the period from 1849 to 1864.